Pemanfaatan Teknologi Aquaponik Tanaman Kangkung dan Budidaya Ikan Lele dalam Ember di Desa Gelam, Kecamatan Candi, Sidoarjo - Binti Azizatun Nafi’ah; Ahmad Bagus Rohim; Desnita Mazaya Choirunisa; Fadia Hana Khairani; Fernanda Putri Jelita; Mochammad David Hardiansyah; Cyntya Dwi Permata; Sisilia Srikandi Mukti; Elvi Anggino Erzon; Reiga El Rafif; Anggie Devitasari (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Aquaponics technology integrates aquaculture and hydroponics, utilizing space and resources efficiently for fish and plant cultivation. This community service program introduces aquaponics technology based on "Budikdamber" (fish farming in a bucket) in Gelam Village, Candi District, Sidoarjo. The activity aims to enhance community skills in utilizing environmentally friendly technology and supporting local food security. The training provided involves the creation of a simple aquaponics system with catfish and water spinach, which can be implemented in small spaces. As a result, the people of Gelam Village showed high enthusiasm for this technology, demonstrating great potential for sustainable agricultural development. The implementation of this aquaponics system is expected to provide economic added value and serve as an example for other villages.